2022
DOI: 10.1371/journal.pgph.0001188
|View full text |Cite
|
Sign up to set email alerts
|

Post-COVID-19 syndrome risk factors and further use of health services in East England

Abstract: Post-COVID syndrome, defined as symptoms persisting for more than twelve weeks after the diagnosis of COVID-19, has been recognised as a new clinical entity in the context of SARS-CoV-2 infection. This study was conducted to characterise the burden and predictors for post-COVID-19 syndrome in the local population. It was a community-based web-survey study conducted in Norfolk, East England, UK. We sent the survey to patients with confirmed COVID-19 infection by real-time polymerase chain reaction by December 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
7
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 7 publications
7
7
0
4
Order By: Relevance
“…We report that 6% of participants still had long COVID at 24 months’ follow-up, which if true in the general population, means that millions of people globally who acquired SARS-CoV-2 infection in 2020 may still be experiencing long COVID 2 years or more after infection. Other studies have reported associations of long COVID with obesity [ 28–30 ] and hyperlipidemia [ 31 ], which we observe as well. We did not observe a relationship between sex assigned at birth and long COVID, as described in other studies [ 1 , 28 , 29 , 32 ], which may be due to sample size.…”
Section: Discussionsupporting
confidence: 89%
“…We report that 6% of participants still had long COVID at 24 months’ follow-up, which if true in the general population, means that millions of people globally who acquired SARS-CoV-2 infection in 2020 may still be experiencing long COVID 2 years or more after infection. Other studies have reported associations of long COVID with obesity [ 28–30 ] and hyperlipidemia [ 31 ], which we observe as well. We did not observe a relationship between sex assigned at birth and long COVID, as described in other studies [ 1 , 28 , 29 , 32 ], which may be due to sample size.…”
Section: Discussionsupporting
confidence: 89%
“…The PRISMA flowchart for study selection is available in eFigure 1 in Supplement 1. The Table summarizes the population cohorts and the study design characteristics of all the included studies . Of the 41 observational studies, 30 were ranked as high quality and 11 moderate quality on the Newcastle-Ottawa Scale (eTable 1 in Supplement 1).…”
Section: Resultsmentioning
confidence: 99%
“…No differences in ROS levels are found between males with ME/CFS or LC, compared to control males (Figure 1E, bottom row) (males ME/CFS v. HC: CD19 B cells p = 0.357, CD4 T cells p = 0.469, CD8 T cells p = 0.516; males ME/CFS v. LC: CD19 B cells p = 0.278, CD4 T cells p = 0.643, CD8 T cells p = 0.583). Notably, our data offers one potential way to interpret several epidemiological studies 31-34 that compare post-COVID 19 and ME/CFS symptoms incidence between males and females. These studies estimate that ME/CFS is three to four times more common in women than men 31 , with significantly higher likelihood for females to develop post COVID-19 symptoms 32-34 (e.g., 3.3x odds ratio estimate for LC in females v. males in Ref.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, our data offers one potential way to interpret several epidemiological studies 31-34 that compare post-COVID 19 and ME/CFS symptoms incidence between males and females. These studies estimate that ME/CFS is three to four times more common in women than men 31 , with significantly higher likelihood for females to develop post COVID-19 symptoms 32-34 (e.g., 3.3x odds ratio estimate for LC in females v. males in Ref. 32).…”
Section: Resultsmentioning
confidence: 99%